KAJIAN ETNOBOTANI PERUBAHAN FUNGSI LAHAN, SOSIAL DAN INISIATIF KONSERVASI MASYARAKAT PULAU ENGGANO - Mohammad Fathi Royyani; Vera Budi Lestari; Oscar Efendy (Research Center for Biology-Indonesian Institute of Sciences, 2017)
This research aims to see the land use change within ethnobotanical perspective. According to observation, interview, and Participatory Rural Appraisal (PRA) it was known that land in Enggano Island have been changed, even the sacred forest transformed, into kebun/garden and ladang/field. The changes of land use was related with demography, economic, and socio-cultural changes in society. Social change affected the species that were planted by the community. The species with a high economic value and a quick harvest and did not need extra treatment planted by local people to replace the previous plants. The other impact that arises is the exixtence of local initiative to restore areas that should functioned as a forest.